Analysis of the relevance between higher education graduates and job opportunities in the digital technology era in Indonesia - Mohdari Mohdari; Tajeri Tajeri; Tania Jannah; Syafril Syafril (Jurnal Bisnis Mahasiswa, 2025)
This study aims to analyze the relevance of higher education graduates to job opportunities in the digital technology era in Indonesia. This study uses a descriptive exploratory approach with a literature review method and direct observation of the research object. The literature review method is conducted by searching for research data or information through reading scientific journals, reference books, and published materials available in libraries and on the internet. This study also uses direct participant observation techniques, conducted by researchers on both employed and unemployed college graduates. The results of this study indicate that the relevance of higher education has a positive impact on job opportunities for some graduates who equip themselves with skills during their studies. From this research, it is hoped that the government and higher education institutions can improve the quality of higher education institutions and also the human resources (HR) of their graduates with the skills needed by the workforce to compete globally.